Association between time of hospitalization with acute myocardial infarction and in-hospital mortality. (29th January 2019) - Wu, Jianhua; Hall, Marlous; Dondo, Tatendashe B; Wilkinson, Chris; Ludman, Peter; DeBelder, Mark; Fox, Keith A A; Timmis, Adam; Gale, Chris P
Abstract: Aims: To study the association between time of hospitalization and in-hospital mortality for acute myocardial infarction (AMI). Methods and results: Patients admitted with ST-elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) across 243 hospitals in England and Wales between 1 January 2004 and 31 March 2013 were included. The outcome measure was in-hospital mortality. Adjusted odds ratios (ORs) for in-hospital mortality were estimated across six 4-hourly time periods over the 24-h clock using multilevel logistic regression, inverse-probability weighting propensity score, and instrumental variable analysis. Among 615 035 patients [median age 70.0 years, interquartile range 59.0–80.0 years; 406 519 (66.0%) men], there were 52 777 (8.8%) in-hospital deaths. At night, patients with NSTEMI were more frequently comorbid, and for STEMI had longer symptom-onset-to-reperfusion times. For STEMI, unadjusted in-hospital mortality was highest between 20:00 and 23:59 [4-h period range 8.4–9.9%; OR compared with 00:00–03:59 reference 1 .13, 95% confidence interval (CI) 1.07–1.20], and for NSTEMI highest between 12:00 and 15:59 (8.0–8.8%; OR compared with 00:00–03:59 reference 1 .07, 95% CI 1.03–1.12). However, these differences were only apparent in the earlier years of the study, and were attenuated by adjustment for demographics, comorbidities, and clinical presentation. Differences were not statistically significant after adjustment for acute clinical treatment provided. Conclusion: There is little evidence to support an association between time of hospitalization and in-hospital mortality for AMI; variation in in-hospital mortality may be explained by case mix and the use of treatments.